2021
DOI: 10.1093/jamiaopen/ooab091
|View full text |Cite
|
Sign up to set email alerts
|

Key requirements of a video-call system in a critical care department as discovered during the rapid development of a solution to address COVID-19 visitor restrictions

Abstract: The COVID-19 pandemic necessitated stringent visitor restrictions in critical care departments worldwide, creating challenges in keeping family members connected to patients and clinical staff. Previous studies have examined how hospitals addressed this challenge by repurposing existing tele-ICU systems or by using personal smartphones as a workaround and have analyzed clinical and family feedback. This case report addresses the experience of rapidly implementing a video-call system in the critical care depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…In 19 studies, video calls were used for virtual visits between patients and families (Dainty et al, 2023;Dhahri et al, 2021;Dhala et al, 2020;Dürst et al, 2022;Ehrler et al, 2021;Kebapcı & Türkmen, 2022;Moolla et al, 2020;Moraes & Chiaradia Mendes-Castillo, 2023;Nicholas et al, 2011;Padua et al, 2021;Parsapour et al, 2011;Ranu et al, 2021;Rose et al, 2021;Rose, Cook, et al, 2022;Sanfilippo et al, 2022;Thomas et al, 2021;Wong & Merchant, 2021;Yang et al, 2014;Yuan et al, 2023), and between patients, families and healthcare professionals in 24 studies (Bansal et al, 2022;Bavare et al, 2021;Bettini, 2020;Carlucci et al, 2020;Cherniwchan, 2022;Chua, 2022;Conroy et al, 2021;de Havenon et al, 2015;Dol et al, 2017;Elma et al, 2022;Epstein et al, 2017;Galazzi et al, 2021;Giuseppe et al, 2022;Kennedy et al, 2021;Nelson et al, 2022;Otte et al, 2022;Rose et al, 2021;Rose, Graham, et al, 2022;Sasangohar et al, 2021;Shunker, 2022;Webb et al, 2020;…”
Section: Characteristics Of the Intervention Studiedmentioning
confidence: 99%
See 3 more Smart Citations
“…In 19 studies, video calls were used for virtual visits between patients and families (Dainty et al, 2023;Dhahri et al, 2021;Dhala et al, 2020;Dürst et al, 2022;Ehrler et al, 2021;Kebapcı & Türkmen, 2022;Moolla et al, 2020;Moraes & Chiaradia Mendes-Castillo, 2023;Nicholas et al, 2011;Padua et al, 2021;Parsapour et al, 2011;Ranu et al, 2021;Rose et al, 2021;Rose, Cook, et al, 2022;Sanfilippo et al, 2022;Thomas et al, 2021;Wong & Merchant, 2021;Yang et al, 2014;Yuan et al, 2023), and between patients, families and healthcare professionals in 24 studies (Bansal et al, 2022;Bavare et al, 2021;Bettini, 2020;Carlucci et al, 2020;Cherniwchan, 2022;Chua, 2022;Conroy et al, 2021;de Havenon et al, 2015;Dol et al, 2017;Elma et al, 2022;Epstein et al, 2017;Galazzi et al, 2021;Giuseppe et al, 2022;Kennedy et al, 2021;Nelson et al, 2022;Otte et al, 2022;Rose et al, 2021;Rose, Graham, et al, 2022;Sasangohar et al, 2021;Shunker, 2022;Webb et al, 2020;…”
Section: Characteristics Of the Intervention Studiedmentioning
confidence: 99%
“…For example, studies suggested that assigning local champions on the hospital wards was a crucial step in implementation (Moolla et al, 2020;Thomas et al, 2021). Training of healthcare professionals was also considered important to help them understand, use and explain video call services (Cherniwchan, 2022;Conroy et al, 2021;Galazzi et al, 2021). Furthermore, adequate and easy-to-use devices and instruction guides were mentioned as technical facilitators for implementing video call services in hospital wards (Bavare et al, 2021;Ranu et al, 2021;Thomas et al, 2021).…”
Section: Facilitatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the beginning of the COVID-19 health crisis, different stakeholders have shown an increasing interest in innovative remote communication solutions and TRs [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, thus far, there is limited available evidence concerning the implementation and usefulness of TRs in a home-dwelling OA population.…”
Section: Trs: a Solution That Has Not Been Thoroughly Studied For Sen...mentioning
confidence: 99%